THE ISSUE OF KAZAKH REFUGEES IN THE 1920S–1930S IN FOREIGN HISTORIOGRAPHY (Journal of history-rus, 2025)
In the article, the author analyzes the manifestations in foreign historiography of the problem of Kazakh refugees during the famine that occurred as a result of the collectivization policy in the 20-30s of the twentieth century. In particular, the works of American, European, as well as Japanese and Russian scientists who conducted research on Kazakh refugees and considered them in chronological order are considered. Gives individual characteristics, paying special attention to the context of writing and the actual bases of work of each foreign scientist. The data and judgments of foreign scientists on the research topic are analyzed. The positions in their works were compared with each other and thus an opportunity was obtained to take a fresh look at this problem.In the article, the author also classifies the research of foreign scientists as works that used archival materials from post-Soviet countries and Chinese archival materials, making judgments, reflecting semantic, positional differences between them.The article also analyzes the thoughts of some foreign scientists regarding the positions of local authorities in relation to Kazakh refugees in the 20-30 years of the twentieth century. Their methods of determining the number of Kazakhs who left their native lands forever are revealed.In the final part, the author formulates his own independent judgments based on the results obtained.